2013
DOI: 10.1111/tmi.12123
|View full text |Cite
|
Sign up to set email alerts
|

Have we improved use of medicines in developing and transitional countries and do we know how to? Two decades of evidence

Abstract: Abstractobjective To assess progress in improving use of medicines in developing and transitional countries by reviewing empirical evidence, 1990-2009, concerning patterns of primary care medicine use and intervention effects.methods We extracted data on medicines use, study setting, methodology and interventions from published and unpublished studies on primary care medicine use. We calculated the medians of six medicines use indicators by study year, country income level, geographic region, facility ownershi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
115
11
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(157 citation statements)
references
References 13 publications
22
115
11
9
Order By: Relevance
“…Although China has implemented a zero drug profit policy since 2009, which aimed at removing profits on drug sales of health facilities, the connection between drug companies and individual doctors still contributes to this problem [18,19]. Compared with more developed regions, healthcare providers in less developed regions had lower incomes, experienced relaxed regulations, and were more likely to profit from overprescribing antibiotics [7,15,20]. Our findings also indicated that, even when doctors were initially unwilling to prescribe antibiotics, more students pressured doctors to prescribe antibiotics in less developed regions compared to developed regions [16,21].…”
Section: Discussionmentioning
confidence: 99%
“…Although China has implemented a zero drug profit policy since 2009, which aimed at removing profits on drug sales of health facilities, the connection between drug companies and individual doctors still contributes to this problem [18,19]. Compared with more developed regions, healthcare providers in less developed regions had lower incomes, experienced relaxed regulations, and were more likely to profit from overprescribing antibiotics [7,15,20]. Our findings also indicated that, even when doctors were initially unwilling to prescribe antibiotics, more students pressured doctors to prescribe antibiotics in less developed regions compared to developed regions [16,21].…”
Section: Discussionmentioning
confidence: 99%
“…As rasuras e emendas estavam presentes em 3,6% das prescrições analisadas (Tabela 2). Os resultados encontrados e dados provenientes de outros estudos [13,18] foram agrupados na Tabela 4, visando estabelecer uma análise comparativa.…”
Section: Resultsunclassified
“…Os indicadores da OMS referentes à prescrição de medicamentos pelo nome genérico e presentes nas LME apresentaram bons resultados na região estudada, principalmente quando comparados aos resultados obtidos em outros estudos nacionais ou internacionais, em que as porcentagens de adequação ao critério não ultrapassavam 90% [9,13,19,20]. A adesão a esses critérios pode ter impacto na redução de custos com a medicação para o usuário, além de proporcionar o acesso a medicamentos seguros e com eficácia terapêutica comprovada para as principais necessidades de saúde da população [21].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The option to go on the more expensive second-line and third-line therapy increases the cost with serious consequences on the provision of healthcare especially in the developing and middle income countries . It has previously been reported that inappropriate use of antibiotics may be escalated by limited adherence to guidelines among physicians in a number of countries and non-adherence to guidelines is thought to be more prevalent among physicians in the public sector (40%) than private-forprofit sector facilities at <30% (Holloway et al, 2013;MdRezal et al, 2015). A study in Malaysia's private ambulatory care clinics (third highest category facility) showed high antibiotics utilisation compared to public primary health care centres (WHO, 2012).…”
Section: Discussionmentioning
confidence: 99%